2013
DOI: 10.5558/tfc2013-112
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of moisture content and basic specific gravity in black spruce logs using a hand-held MEMS-based near-infrared spectrometer

Abstract: Our study presents results of a test of a hand-held micro-electro-mechanical system (MEMS)-based near-infrared (NIR) spectrometer to estimate moisture content and basic specific gravity of black spruce frozen and unfrozen logs. The spectra were acquired on sapwood and heartwood as well as on tangential and transversal log sections. Partial least square regression was used to develop and validate the models that relate NIR spectral data to the log properties. Models were developed for the frozen and unfrozen lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Indeed, temperature variations produce changes in band shapes by changing the weaker inter-and intra-molecular forces (Wulfert et al 2000).The average shift of the maximum absorbance peak (around 1450 nm) in our data is 8.6 nm for the sapwood and 25.8 nm for the heartwood. Hans et al (2013) reported an opposite tendency for the shift between thawed and frozen wood spectra of black spruce sapwood and heartwood with values of 17.2 and 8.6 nm, respectively. Using FT-NIR spectra acquired from Norway spruce (Picea abies (L.) H. Karst) planed square samples, Thygesen and Lundqvist (2000a) reported a shift of 39 nm for the sapwood and 19 nm for the heartwood when the temperature decreased from 20a°C to −15°C.…”
Section: Nir Spectramentioning
confidence: 96%
“…Indeed, temperature variations produce changes in band shapes by changing the weaker inter-and intra-molecular forces (Wulfert et al 2000).The average shift of the maximum absorbance peak (around 1450 nm) in our data is 8.6 nm for the sapwood and 25.8 nm for the heartwood. Hans et al (2013) reported an opposite tendency for the shift between thawed and frozen wood spectra of black spruce sapwood and heartwood with values of 17.2 and 8.6 nm, respectively. Using FT-NIR spectra acquired from Norway spruce (Picea abies (L.) H. Karst) planed square samples, Thygesen and Lundqvist (2000a) reported a shift of 39 nm for the sapwood and 19 nm for the heartwood when the temperature decreased from 20a°C to −15°C.…”
Section: Nir Spectramentioning
confidence: 96%
“…They showed MC predictions for conditioned samples within 2-3% of measured values in the 0-30% MC range. Hans et al (2012) applied NIR spectroscopy for estimating MC of frozen and unfrozen black spruce logs. They acquired spectra on sapwood and heartwood as well on tangential and transversal log sections and developed predictive models for the frozen and unfrozen logs separately (temperature-specific models) and for both kinds of logs together (generalized model).…”
Section: Moisture Contentmentioning
confidence: 99%
“…Their study demonstrated that the wavelength range and resolution of the portable instruments are adequate showing promising results and pointing out that the properties (wavelength range and resolution) of the portable instruments are suitable for the prediction of Kraft pulp yield and cellulose content. Hans et al (2012) tested a hand-held microelectro-mechanical system (MEMS) based on NIR spectrometer to estimate moisture content and basic specific gravity of frozen and unfrozen black spruce logs. They stated that this type of spectrometer apparatus can be used independently of temperature and freezing conditions.…”
Section: Practical Aspects In Wood Nir Measurements Laboratory Vs Pomentioning
confidence: 99%
“…Knots present a higher density than normal wood. Depending on the studies and methods used, knots can be included in the models (Mora et al 2011a) or not (Hans et al 2012). Decay is a major matter of concern in the wood industry because it reduces wood strength and is particularly difficult to detect.…”
Section: Principles Of Nir Spectroscopymentioning
confidence: 99%
“…The second solution is to build a generalized model based on spectra collected for all the temperatures. Hans et al (2012) reported that PLS models developed for predicting moisture content and density for frozen and unfrozen logs of black spruce (Picea mariana [Mill.] BSP) using NIR spectra gave similar prediction accuracy with R 2 of 0.91, 0.84 and 0.89, respectively, for unfrozen, frozen logs and both types of logs.…”
Section: Principles Of Nir Spectroscopymentioning
confidence: 99%